PENGARUH STRATEGI PQ4R DISERTAI MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA MATERI ORGANISASI KEHIDUPAN DI SMP - Wahyuni, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aim to determine the effect of PQ4R learning strategy with mind mapping on learning outcomes of students in material of Life Organization in the seventh grade of SMP Negeri 2 Semparuk. This research was quasi-experimental design with non-equivalent control group design.The research samples was class VIIA as the experimental class and VIIB as the control class, with a sampling technique of intact group. The instrument was used the multiple choice test with a total of 20 questions. The averages of students learning outcome in the experimental class was 15.26, while the control group was 12.88. The results of the U Mann-Whitney test analysis showed that Zcount<-Ztable (-3.63<-1.96), it is mean that there were significant differences between the learning outcome of students taught using PQ4R learning strategy with mind mapping and the learning outcomes of students taught using a expository learning strategy. The effect size value obtained was 0.72 with falling into the moderate category, and contributed to 26.42%. Keywords: PQ4R strategy with mind mapping, learning outcome, life organization